(untitled) (Research, Society and Development, 2023)
Nanomaterials (NMs) can exhibit physical, chemical, and biological properties different from their counterparts at the micro or larger scale, molecular, or atomic level. Altering these properties may modify or intensify the toxicological effects of NMs on living organisms and the environment. The distinct properties of NMs have expanded their potential applications in various technological areas, leading to a significant increase in production. Consequently, the number of researchers exposed to NMs in laboratories has also increased. The aim of this study is to identify the most suitable method for assessing occupational risks in research laboratories working with nanomaterials. To achieve this, risk assessment methods focusing on control through risk levels (control banding - CB) were selected and applied to research laboratories in three different tasks (processes), and the results were compared. In general, there is convergence between the methods regarding their results for each of the studied tasks. However, under these conditions, only one method met both comparison criteria: CB IMEC.